ECOBLOCK -Transforming a large scale housing block into an urban ecovillage - Malm, Julia (My University, 2020)
In Gothenburg there is a current lack in housing that needs to be resolved through a production of more homes. At the same time the building industry causes more than one fifth of the total greenhouse emissions in Sweden which must be considered when proposing new development (Boverket, 2017). Another cause of greenhouse emission is household consumption, which the city of Gothenburg has a goal of reducing. This too needs consideration. To tackle these issues this thesis proposes that we need to look at development with a holistic solution concerning housing such as (urban) ecovillages. This typology of housing community can provide a framework which can help to ensure that the final project considers all aspects of sustainability; social, cultural, ecological and economical. The aim of this thesis was to develop a proposal for such a housing community. Site, program and design of the proposed development have been concluded through an investigation and evaluation process. Each choice of solution is presented and argued for in respect to negative and positive impact. The resulting proposal is to add an urban ecovillage containing housing and communal program to the roof of an existing building while, at the same time improving the housing situation for the current residents of said building. This strategy of development could help densify the city, lower costs of housing and lower emissions in connection with construction. A program of communal spaces that offer the possibility to share resources could also lower emissions in connection with household consumption. This thesis concludes that the proposed transformation is a feasible way of sustainable development with positive impact socially, economically and ecologically. New forms of housing should improve the situation for all people in society so that eco living is not just for an elite group.
Keywords: urban ecovillage, housing, sharing economy, community, low impact